Proceeding of the 11th World Congress on Intelligent Control and Automation 2014
DOI: 10.1109/wcica.2014.7053313
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and optimization of a vehicle crash test based on a single-mass

Abstract: In this paper mathematical modelling of a vehicle crash test based on a single mass is studied. The models under consideration consist of a single mass, a spring and/or a damper. They are constructed according to the measured vehicle speed before the collision and measured vehicle accelerations in three directions at the centre of gravity. A new model of nonlinear spring-mass-damper is also proposed to describe the crash.Simulation results are provided to show the effectiveness and applicability of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In recent years, the explicit non-linear finite element analysis (FEA) has emerged as, undoubtedly, the most widely renowned modelling approach in EV crashworthiness due to its high accuracy in material specifications, stresses, and deformation during the impact [73]. The aspects of analyses include the structural behavior of the vehicle and mechanisms for protecting against high-voltage.…”
Section: Recent Research On Crashworthiness Of Evsmentioning
confidence: 99%
“…In recent years, the explicit non-linear finite element analysis (FEA) has emerged as, undoubtedly, the most widely renowned modelling approach in EV crashworthiness due to its high accuracy in material specifications, stresses, and deformation during the impact [73]. The aspects of analyses include the structural behavior of the vehicle and mechanisms for protecting against high-voltage.…”
Section: Recent Research On Crashworthiness Of Evsmentioning
confidence: 99%
“…Different forms are configured and used in analyzing the crash response. For instance, the basic lumped mass model consists of masses and linear springs [1], LPM including beam elements, plastic hinges, nonlinear contact spring elements, and rigid solids [2], and models using nonlinear spring and damper [3,4]. However, considering the mathematical complexity of a crash event representation, it was concluded that the determination of the force elements in the mathematical model has a remarkable influence on response prediction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the authors proposed an approach to control the seat belt restraint system force during a frontal crash to reduce thoracic injury. Klausen et al [10,11] introduced a firefly optimisation method to estimate parameters of vehicle crash test based on a single mass-spring-damper model. Ofochebe et al [12] studied the performance of a vehicle front structure using a 5-DOF lumped mass-spring model composed of body, engine, the cross-member, the suspension, and the bumper masses.…”
Section: Introductionmentioning
confidence: 99%
“…Although LPMs have been extensively used for reconstruction of crash scenario at specific impact velocity, it is still worthy to explore more the use of LPM, for predicting the crash event at various impact velocities as a complement to the existing results e.g., in [11,33,34]. In this paper, the authors investigate whether it is possible to accurately estimate the basic crashworthiness parameters such as maximum dynamic crush and ASI, using the earlier proposed LPM [13,14].…”
Section: Introductionmentioning
confidence: 99%